Developing Math Modules to Improve Students' Mathematical Literacy - Rissa Virga Kandira; Afifah Nur Aini (Educational Insights, 2025)
This study aims to produce a module to improve students' mathematical literacy. This study is a Research and Development (R&D) using the ADDIE model which includes: (1) analysis, (2) design, (3) development, (4) implementation, and (5) evaluation. The subjects in this study were 20 students of class VIIIE of SMP Negeri 02 Wuluhan. The instruments used were a module validity questionnaire, a module practicality questionnaire, and an effectiveness test device in the form of pre-test and post-test questions. The results of the pre-test and post-test were tested using the paired sample t-test. The results showed that the module achieved an average validity of 93.7% (very valid), and a practicality of 98.47% (very practical). The Paired Sample T-Test showed a significant difference between the pre-test and post-test results (sig. 0.000 <0.05) with an increase in mathematical literacy scores of 33.57. So, it can be concluded that the module is valid, practical, and effective in improving students' mathematical literacy.